If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 7t + 8 Reorder the terms: 1 = 8 + 7t Solving 1 = 8 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 1 + -7t = 8 + 7t + -7t Combine like terms: 7t + -7t = 0 1 + -7t = 8 + 0 1 + -7t = 8 Add '-1' to each side of the equation. 1 + -1 + -7t = 8 + -1 Combine like terms: 1 + -1 = 0 0 + -7t = 8 + -1 -7t = 8 + -1 Combine like terms: 8 + -1 = 7 -7t = 7 Divide each side by '-7'. t = -1 Simplifying t = -1
| 15+4k=-57 | | 2x+4+62=180 | | -20-13x=-371 | | 7+7b=35 | | -45=7-2p | | 19=23-4b | | Log(x+14)-log(x+6)=logx | | t-3=13 | | 13+7v=97 | | 3(x-7)=x-6 | | 105-3h=69 | | 6x+16=5x+9 | | 1.5(x-24)=13 | | f(-3)=6x^2-12 | | 4(3z-5)+9(5z+4)= | | 16=3d+1 | | 5-25x=105 | | 99=7j+1 | | x^2-5y^2=3 | | 2=3y-18-5x | | x^2-9+2xy+y+5=10 | | 67=25+6s | | -13+a=-6 | | 15-2x-7=14 | | 2-2m=8 | | 67=256s | | -x(x^2+4)= | | 7s-10=46 | | 26=3u-64 | | E^3-2x=10 | | 2y+4=4y-6 | | 38k=2204 |